EFEKTIVITAS PUPUK ORGANIK CAIR DAN PUPUK NPK PADA PERTUMBUHAN DAN HASIL TANAMAN CABAI - Rini Suryani; Rizky Septika Utami (Fakultas Pertanian Universitas Ratu Samban, 2025)
Chili pepper (Capsicum annuum L.) is a high economic value horticultural commodity that requires optimal nutrient availability to support vegetative growth and fruit formation. Fertilization is a key factor in increasing chili productivity, both through the use of inorganic fertilizers such as NPK and liquid organic fertilizer (LOF). This literature review discusses the role and effectiveness of LOF and NPK application on the growth and yield of chili plants. The review findings show that NPK supplies the primary macronutrients nitrogen, phosphorus, and potassium, which function in chlorophyll formation, root development, flowering, and increased fruit production. LOF contributes to improving soil properties, enhancing microbial activity, and supplying micronutrients. The combination of LOF and NPK is considered more effective than single use because it increases nutrient uptake efficiency and supports sustainable agriculture. However, further research is needed regarding LOF quality standards and the optimum dosage of the combination for chili cultivation.